A case of vaccine‐associated myocarditis following pneumococcal immunization leading to acute mitral regurgitation - Hiroyuki Yamamoto; Marie Takahashi; Jun Isogai (ESC Heart Failure)
Abstract Vaccine‐associated myocarditis (VAM) is a rare entity but can result in potentially serious sequelae if left untreated. However, the mechanisms of the complications of VAM and its treatment remain unclear. Herein, we report the first case of VAM related to pneumococcal immunization, presenting as a local and systemic inflammatory reaction, in which the patient developed significant secondary mitral regurgitation, resulting in acute heart failure. Finally, the patient recovered completely following corticosteroid treatment. This case highlights the value of cardiac magnetic resonance and the pitfall of endomyocardial biopsy in establishing the definitive diagnosis of VAM and emphasizes the importance of optimal management in understanding the mechanism and instituting the treatment for secondary mitral regurgitation caused by VAM.